Chronologically matched toenail-Hg to hair-Hg ratio: temporal analysis within the Japanese community (U.S.) - Hinners Thomas; Tsuchiya Ami; Stern Alan H; Burbacher Thomas M; Faustman Elaine M; Mariën Koenraad (BMC, 2012)
Abstract Background Toenail-Hg levels are being used as a marker of methylmercury (MeHg) exposure in efforts to associate exposure with effects such as cardiovascular disease. There is a need to correlate this marker with more established biomarkers that presently underlie existing dose-response relationships in order to compare these relationships across studies. Methods As part of the Arsenic Mercury Intake Biometric Study, toenail clippings were collected at three time points over a period of one year amongst females from within the population of Japanese living near Puget Sound in Washington State (US). Variability in temporal intra-individual toenail-Hg levels was examined and chronologically matched hair and toenail samples were compared to more accurately define the toxicokinetic variability of Hg levels observed between the two compartments. Results Mean toenail-Hg values (n=43) for the 1st, 2nd and 3rd visits were 0.60, 0.60 and 0.56 ng/mg. Correlations were as follows: r=0.92 between 1st and 2nd clinic visits, r=0.75 between 1st and 3rd visits and r=0.87 between 2nd and 3rd visits. With few exceptions, toenail-Hg values from any visit were within 50-150% of the individual's mean toenail-Hg level. Nearly all participants had less than a two-fold change in toenail-Hg levels across the study period. A regression model of the relationship between toenail-Hg and hair-Hg (n = 41) levels representing the same time period of exposure, gave a slope (Hg ng/mg) of 2.79 for hair relative to toenail (r=0.954). Conclusions A chronologically matched hair-Hg to toenail-Hg ratio has been identified within a population that consumes fish regularly and in quantity. Intra-individual variation in toenail-Hg levels was less than two-fold and may represent dietary-based fluctuations in body burden for individuals consuming various fish species with different contaminant levels. The chronologically matched ratio will be useful for relating MeHg exposure and dose-response derived from toenail-Hg measurements to those derived from hair-Hg measurements in other studies, and may be useful in future investigations as an indicator of stable MeHg body burden within a population.